Lo terrorífico-gótico en el Teatro caliente de Francisco Nieva - Falska, Maria (Romanica Silesiana)
In Francisco Nieva’s works, all dramatic components reflect the elements of the supernatural. It can be observed in the construction of the dramatic situation, in the action, the characters, space relationships, and in the visual as well as acoustic signs in the performance. This paper aims at analysing the elements of the extraordinary and fantastic such as ‘terror’ by which the author creates the atmosphere of dread. The analysis focuses on Nieva’s recent works collected in Teatro caliente and published in 2013. Deriving from the definition of terror, the paper further examines various devices implemented in order to evoke the sense of fear of obscure and dreadful details. Among these are some of the elements characteristic of the genre of the gothic novel. Key words: Nieva, Teatro caliente, terror, gothic